Circuit board
A circuit board design using polyarylene sulfide resin and a thermoplastic resin with a styrene elastomer adhesive layer addresses adhesion issues in high-frequency applications, enhancing durability and reducing transmission loss.
Patent Information
- Application Number
- JP2023106942
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Circuit boards using engineering plastic resins for insulating materials face issues with adhesive strength, leading to blistering and peeling during reflow processes due to poor adhesion between the insulating base material and the adhesive layer, which is exacerbated by high-frequency signal transmission.
A circuit board structure comprising a polyarylene sulfide resin as the main component for the insulating base material, combined with a thermoplastic resin and a styrene elastomer adhesive layer, ensures improved adhesion and reduced transmission loss by laminating layers with specific components and properties.
The solution enhances reflow resistance and reduces transmission loss at high frequencies by improving adhesion between layers, resulting in durable and efficient circuit boards.
Smart Images

Figure 2025006261000001 
Figure 2025006261000002 
Figure 2025006261000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a circuit board comprising a laminate in which an insulating base material made of a resin composition containing as a main component a polyarylene sulfide-based resin having excellent adhesive properties and low dielectric properties is laminated with a low dielectric adhesive layer. [Background technology]
[0002] In recent years, in electronic devices such as personal computers and mobile terminals, the frequency of electrical signals is increasing with the increase in communication speed and capacity, and printed wiring boards that can handle this are required. In particular, the higher the frequency of the electrical signal, the greater the loss (attenuation) of signal power, and printed wiring boards that can reduce the loss of signal power (transmission loss) are required. Transmission loss includes conductor loss on the copper foil side that serves as a conductor and dielectric loss on the board side. To reduce conductor loss, it is preferable to reduce the surface roughness of the copper foil that serves as a conductor, since there is a skin effect in the high frequency range and the signal has the characteristic of flowing on the surface of the conductor. On the other hand, to reduce dielectric loss, it is preferable for the resin base material and adhesive to have low dielectric properties. Printed wiring boards made of materials that satisfy these properties are required as circuit boards with low transmission loss.
[0003] Cited Document 1 discloses a circuit board that uses polyether ether ketone, liquid crystal polymer, fluororesin, cycloolefin polymer, or polyphenylene sulfide resin as a resin substrate, has a conductor circuit on the substrate surface, and uses a low dielectric adhesive for the adhesive layer, and thus discloses a circuit board with low transmission loss. However, the resin used in the resin substrate is an engineering plastic resin, which generally has poor adhesive properties, and there is no description of its adhesive properties with the adhesive layer, and there is a possibility that swelling and peeling may occur during reflow. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-39457 Summary of the Invention [Problem to be solved by the invention]
[0005] In a circuit board composed of an insulating base material, a metal layer, and an adhesive layer having low dielectric properties, if the insulating base material is made of an engineering plastic resin such as polyphenylene sulfide resin, which is difficult to bond to, the adhesive strength with the adhesive layer is insufficient, and there is a problem that swelling and peeling occur during reflow. The present invention provides a high-frequency compatible circuit board with excellent reflow resistance and low transmission loss. [Means for solving the problem]
[0006] As a result of sincere investigation, the inventors have found that the above-mentioned problems can be solved by laminating, in this order, at least a metal layer (I); an insulating substrate (I) having circuits formed on one or both sides thereof, which is made of a resin composition of a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than the polyarylene sulfide-based resin (A) having a glass transition temperature of 140°C or more or a melting point of 230°C or more; an adhesive layer having a specific component on the circuit-forming side; and an insulating substrate (II) or a metal layer (II), and have completed the present invention. That is, the present invention relates to the following (1) to (11).
[0007] (1) A circuit board including at least a metal layer (I), an insulating substrate (I) having a circuit formed on one or both sides thereof, an adhesive layer on the circuit forming side, and an insulating substrate (II) or a metal layer (II) laminated in this order, the insulating substrate (I) being made of a resin composition of a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher; The circuit board, wherein the adhesive layer is a thermosetting resin layer containing a styrene-based elastomer. (2) The circuit board according to item 1, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is a dispersed phase having an average dispersed diameter of 5 μm or less. (3) The circuit board according to 1 or 2, wherein the blending ratio of the thermoplastic resin (B) other than the polyarylene sulfide-based resin is in the range of 1 to 49 mass% relative to 100 mass% of the total amount of the polyarylene sulfide-based resin (A) and the thermoplastic resin (B). (4) The circuit board according to any one of 1 to 3, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is a polyphenylene ether resin, a polycarbonate resin, a polyethersulfone resin, a polyphenylsulfone resin, a polyetherimide resin, a polysulfone resin, or a fluorine-containing resin. (5) The circuit board according to any one of 1 to 4, wherein the insulating base material (I) has a dielectric constant of 3.3 or less. (6) The circuit board according to any one of 1 to 5, further comprising a modified elastomer (C) having a reactive group imparted to the resin composition of the insulating base material (I). (7) The circuit board according to 6, wherein the modified elastomer (C) is an olefin polymer having at least one functional group selected from the group consisting of an epoxy group and an acid anhydride group. (8) The circuit board according to 6 or 7, wherein the content of the modified elastomer (C) is 1 to 15 mass% relative to 100 mass% in total of the polyarylene sulfide resin (A), the thermoplastic resin other than polyarylene sulfide (B), and the modified elastomer (C). (9) The circuit board according to any one of 6 to 8, wherein the modified elastomer (C) has an α-olefin content of 50 to 95% by mass based on the total mass of the modified elastomer. (10) The circuit board according to any one of 1 to 9, further comprising 0.01 to 5 mass % of a silane coupling agent (D) containing at least one functional group selected from an epoxy group, an amino group, and an isocyanate group. (11) A high-speed transmission cable comprising the circuit board according to any one of 1 to 10. Effect of the Invention
[0008] According to the present invention, a circuit board is provided in which at least a metal layer (I), an insulating base material (I) having circuits formed on one or both sides, an adhesive layer on the circuit-forming side, and an insulating base material (II) or a metal layer (II) are laminated in this order. By using a resin composition consisting of a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 140°C or more or a melting point of 230°C or more for the insulating base material (I), it is possible to provide a circuit board that has improved adhesion to the adhesive layer containing a styrene-based elastomer, excellent reflow resistance, and reduced transmission loss at high frequencies. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described in detail.
[0010] [Insulating substrate (I)] The resin composition constituting the insulating substrate (I) is mainly composed of a polyarylene sulfide resin (hereinafter sometimes referred to as "PAS resin") and is made of a thermoplastic resin other than polyarylene sulfide resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher. In this case, the resin composition has a continuous phase and a dispersed phase, the continuous phase contains a polyarylene sulfide resin, and the dispersed phase contains a thermoplastic resin (B) other than polyarylene sulfide resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher. In the present invention, the "main component" means that the polyarylene sulfide resin accounts for 51% by mass or more when the entire resin composition is taken as 100% by mass.
[0011] The insulating substrate (I) of the present invention preferably has a dielectric constant of 3.3 or less and a dielectric loss tangent of 0.005 or less at a frequency of 5 GHz. More preferably, the dielectric constant is 3.0 or less and the dielectric loss tangent is 0.004 or less. If the dielectric constant is 3.3 or less and the dielectric loss tangent is 0.005 or less, the insulating substrate (I) can be suitably used for FPC-related products for high frequency applications.
[0012] The average dispersion diameter of the dispersed phase is 5 μm or less, preferably 0.5 μm or more and 5 μm or less, and more preferably 0.5 μm or more and 3 μm or less. If the average dispersion diameter of the dispersed phase is within the range of 0.5 μm or more and 5 μm or less, it is possible to obtain an insulating base material that maintains the physical properties as an insulating base material and has excellent adhesion to metals and adhesive layers. In the present specification, the "average dispersion diameter of the dispersed phase" is a value measured by the method described in the Examples.
[0013] [Polyarylene sulfide resin (A)] The polyarylene sulfide resin (A) (PAS resin (A)) is the main component of the resin composition, and is in principle contained in the continuous phase of the resin composition. The PAS resin (A) is a polymer containing a structure in which an aromatic ring and a sulfur atom are bonded (specifically, a structure represented by the following formula (1)) as a repeating unit.
[0014] [ka] In the above formula, R 1 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group, and each n independently represents an integer of 1 to 4.
[0015] Here, R in the structure represented by formula (1) 1 It is preferable that R is a hydrogen atom. This structure can further increase the mechanical strength of the PAS resin (A). 1 are hydrogen atoms, includes a structure represented by the following formula (2) (i.e., a structure in which a sulfur atom is bonded to an aromatic ring at a para position) and a structure represented by the following formula (3) (i.e., a structure in which a sulfur atom is bonded to an aromatic ring at a meta position).
[0016] [ka] Among these, the structure represented by formula (1) is preferably a structure represented by formula (2). If the PAS resin (A) has the structure represented by formula (2), the heat resistance and crystallinity can be further improved.
[0017] Furthermore, the PAS resin (A) may contain not only the structure represented by the above formula (1) but also structures represented by the following formulas (4) to (7) as repeating units.
[0018] [ka]
[0019] The structures represented by the formulae (4) to (7) are preferably contained in an amount of 30 mol % or less, more preferably 10 mol % or less, of all repeating units constituting the PAS resin (A), which can further increase the heat resistance and mechanical strength of the PAS resin (A). The bonding pattern of the structures represented by formulas (4) to (7) may be either random or block.
[0020] The PAS resin (A) may contain, as a repeating unit, a trifunctional structure represented by the following formula (8), a naphthyl sulfide structure, or the like, in its molecular structure.
[0021] [ka]
[0022] The structure represented by formula (8), naphthyl sulfide structure, etc. are preferably contained in an amount of 1 mol % or less, and more preferably substantially absent, in all repeating units constituting the PAS resin (A). With such a structure, the content of chlorine atoms in the PAS resin (A) can be reduced. The properties of the PAS resin (A) are not particularly limited as long as they do not impair the effects of the present invention. However, the melt viscosity (V6) at 300°C is preferably 100 to 2000 Pa s, and more preferably 120 to 1600 Pa s in order to achieve a good balance between fluidity and mechanical strength.
[0023] Furthermore, it is particularly preferred that the PAS resin (A) has a peak in the molecular weight range of 25,000 to 40,000 when measured by gel permeation chromatography (GPC), has a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) in the range of 5 to 10, and has a non-Newtonian index in the range of 0.9 to 1.3. By using such a PAS resin (A), the chlorine atom content in the PAS resin (A) itself can be reduced to the range of 500 to 2,000 ppm without reducing the mechanical strength of the insulating film 4, facilitating application to halogen-free electronic and electrical component applications.
[0024] In this specification, the weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) are values measured by gel permeation chromatography (GPC). The measurement conditions for GPC are as follows: [Measurement conditions for gel permeation chromatography] Equipment: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000 manufactured by Senshu Scientific Co., Ltd.) Column: UT-805L (Showa Denko) Column temperature: 210℃ Solvent: 1-chloronaphthalene Measurement method: UV detector (360 nm) calibrated with six types of monodisperse polystyrene. The molecular weight distribution and peak molecular weight are measured using the method.
[0025] The method for producing the PAS resin (A) is not particularly limited, but examples thereof include 1) a method in which a dihalogenoaromatic compound, if necessary a polyhalogenoaromatic compound or other copolymerization component is added in the presence of sulfur and sodium carbonate, and polymerized, 2) a method in which a dihalogenoaromatic compound, if necessary a polyhalogenoaromatic compound or other copolymerization component is added in the presence of a sulfidizing agent or the like in a polar solvent, and polymerized, 3) a method in which p-chlorothiophenol, if necessary another copolymerization component is added, and self-condensed, etc. Among these production methods, the above method 2) is versatile and preferred. During the reaction, an alkali metal salt of a carboxylic acid or a sulfonic acid, or an alkali hydroxide may be added to adjust the degree of polymerization.
[0026] Among the above method 2), the following method 2-1) or 2-2) is particularly preferred. In the method 2-1), a water-containing sulfidizing agent is introduced into a mixture containing a heated organic polar solvent and a dihalogeno aromatic compound at a rate at which water can be removed from the reaction mixture, and the dihalogeno aromatic compound and the sulfidizing agent are added, and optionally a polyhalogeno aromatic compound is added, in the organic polar solvent to react with each other, and the amount of water in the reaction system is controlled within a range of 0.02 to 0.5 mol per mol of the organic polar solvent to produce a PAS resin (A) (see JP-A-07-228699). In the method of 2-2), a dihalogeno aromatic compound and, if necessary, a polyhalogeno aromatic compound or other copolymerization component are added in the presence of a solid alkali metal sulfide and an aprotic polar organic solvent, and an alkali metal hydrosulfide and an organic acid alkali metal salt are reacted with each other by controlling the amount of the organic acid alkali metal salt to within a range of 0.01 to 0.9 mol per mol of the sulfur source and controlling the amount of water in the reaction system to within a range of 0.02 mol or less per mol of the aprotic polar organic solvent, thereby producing a PAS resin (A) (see WO2010 / 058713 pamphlet).
[0027] Specific examples of the dihalogeno aromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalodiphenyl sulfoxide, 4,4'-dihalodiphenyl sulfide, and the above compounds each having an alkyl group having 1 to 18 carbon atoms on the aromatic ring. Examples of the polyhalogeno aromatic compounds include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, and 1,4,6-trihalonaphthalene. The halogen atoms contained in the above compounds are preferably chlorine atoms or bromine atoms.
[0028] The reaction mixture containing the PAS resin (A) obtained by the polymerization step can be post-treated by a known method, which is not particularly limited, and may, for example, be any of the following methods (1) to (5): In the method (1), after the polymerization reaction is completed, the solvent is first distilled off under reduced pressure or normal pressure, either directly from the reaction mixture or after addition of an acid or a base, and then the solid matter remaining after the solvent distillation is washed once or twice or more times with a solvent such as water, the reaction solvent (or an organic solvent having an equivalent solubility to the low molecular weight polymer), acetone, methyl ethyl ketone, or an alcohol, and then neutralized, washed with water, filtered, and dried. In the method (2), after the polymerization reaction is completed, a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, or aliphatic hydrocarbons (a solvent that is soluble in the polymerization solvent used and is a poor solvent for at least the PAS resin (A)) is added to the reaction mixture as a precipitating agent to precipitate solid products such as the PAS resin (A) and inorganic salts, which are then filtered, washed, and dried.
[0029] In the method (3), after the polymerization reaction is completed, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer) is added to the reaction mixture and stirred, and then the mixture is filtered to remove the low molecular weight polymer. The mixture is then washed once or twice or more times with a solvent such as water, acetone, methyl ethyl ketone, or alcohols, and then neutralized, washed with water, filtered, and dried. In the method (4), after the polymerization reaction is completed, water is added to the reaction mixture, which is then washed with water, filtered, and if necessary, acid is added during the water washing step for acid treatment, and the mixture is then dried. In the method (5), after the polymerization reaction is completed, the reaction mixture is filtered, washed once or more times with the reaction solvent as required, further washed with water, filtered and dried.
[0030] Examples of acids that can be used in the above method (4) include organic acids such as saturated fatty acids, such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, and monochloroacetic acid; unsaturated fatty acids, such as acrylic acid, crotonic acid, and oleic acid; aromatic carboxylic acids, such as benzoic acid, phthalic acid, and salicylic acid; dicarboxylic acids, such as maleic acid and fumaric acid; and sulfonic acids, such as methanesulfonic acid and paratoluenesulfonic acid; and inorganic acids, such as hydrochloric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, and phosphoric acid. Examples of hydrogen salts include sodium hydrogen sulfide, disodium hydrogen phosphate, sodium hydrogen carbonate, etc. However, in practical use, organic acids are preferred because they are less corrosive to metal members. In the above methods (1) to (5), the PAS resin (A) may be dried in vacuum, in air, or in an atmosphere of an inert gas such as nitrogen.
[0031] In particular, the PAS resin (A) that has been post-treated by the method (4) above has an increased amount of acid groups bonded to its molecular terminals, and when it is mixed with the modified elastomer (C), it has the effect of improving the dispersibility of the two. The acid group is preferably a carboxyl group. The content of the PAS resin (A) in the resin composition may be 50 to 93% by mass, preferably 55 to 90% by mass. If the content of the PAS resin (A) is within the above range, the heat resistance and chemical resistance of the resin layer can be further improved.
[0032] [Thermoplastic resin other than polyarylene sulfide resin (B)] The thermoplastic resin (B) other than the polyarylene sulfide resin (A) of the present invention (hereinafter, sometimes referred to as "thermoplastic resin (B)") may be any thermoplastic resin other than a PAS resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher. If the thermoplastic resin (B) has a glass transition temperature of 140°C or higher or a melting point of 230°C or higher, it is possible to suppress a significant decrease in heat resistance, enhance the surface modification effect by corona treatment and plasma treatment, and improve adhesion. In addition, it is possible to enhance the affinity with the styrene-based elastomer contained in the adhesive layer, and the laminate consisting of the insulating substrate (I) made of the resin composition of the present invention and the adhesive layer has high adhesive strength.
[0033] The thermoplastic resin (B) other than the PAS resin (A) may be any thermoplastic resin having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher, and may be, for example, various polymers such as polycarbonate, polyphenylene ether, polyethersulfone, polyphenylsulfone, polyetherimide, polysulfone, fluorine-containing resin, etc., or a blend containing at least one of these polymers. Among these, polyphenylene ether or fluorine-containing resin is preferred from the viewpoints of low dielectric properties, mixability with PAS, affinity with an adhesive layer containing a styrene-based elastomer, and low moisture absorption.
[0034] The content of the thermoplastic resin (B) in the resin composition constituting the resin layer may be 1 to 49% by mass, but is preferably 3 to 40% by mass. If the content of the thermoplastic resin (B) is within the above range, the physical properties of the insulating substrate are maintained, and the adhesiveness with the adhesive layer is effective.
[0035] Polyphenylene ether resin (hereinafter sometimes referred to as "PPE resin") is a component that has the function of lowering the dielectric constant and dielectric loss tangent of the insulating base material (I), and is preferred because it has high compatibility with the styrene portion of the styrene elastomer contained in the adhesive layer, thereby improving adhesion. The PPE resin is a polymer containing the structure represented by the following formula (9) as a repeating unit.
[0036] [ka]
[0037] In the above formula, R 2 each independently represents a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a haloalkyl group, an aminoalkyl group, a hydrocarbyloxy group, or a halohydrocarbyloxy group in which at least two carbon atoms separate the halogen atom from the oxygen atom, and each m independently represents an integer of 1 to 4.
[0038] Specific examples of PPE resins include homopolymers such as poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), and poly(2,6-dichloro-1,4-phenylene ether), as well as copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol and 2-methyl-6-butylphenol). Among these, the PPE resin is preferably poly(2,6-dimethyl-1,4-phenylene ether) or a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, and more preferably poly(2,6-dimethyl-1,4-phenylene ether).
[0039] The number average molecular weight of the PPE resin is preferably 1,000 or more, more preferably 1,500 to 50,000, and even more preferably 1,500 to 30,000.
[0040] Fluorine-containing resins are preferred as the thermoplastic resin (B) because of their low dielectric properties, and preferably have at least one reactive functional group selected from the group consisting of carbonyl-containing groups, hydroxyl groups, epoxy groups, and isocyanate groups. Two or more of these reactive functional groups may be included. Among them, carbonyl-containing groups are preferred because of their excellent reactivity with the PAS resin (A). Examples of the carbonyl-containing group include groups having a carbonyl group between the carbon atoms of a hydrocarbon group, carbonate groups, carboxy groups, haloformyl groups, alkoxycarbonyl groups, acid anhydride groups, and polyfluoroalkoxycarbonyl groups.
[0041] Methods for introducing reactive functional groups into fluorine-containing resins include: (1) using a monomer having a reactive functional group when producing the main chain of a fluorine-containing resin having a reactive functional group by polymerization reaction; (2) producing a fluorine-containing resin having a functional group by polymerization reaction using a chain transfer agent that generates a radical having a reactive functional group; (3) producing a fluorine-containing resin having a functional group by polymerization reaction using a polymerization initiator that generates a radical having a reactive functional group; (4) modifying a fluorine-containing resin by a technique such as oxidation or thermal decomposition; and (5) blending a compound or resin that is compatible with the fluorine-containing resin and contains the functional group.
[0042] Examples of the reactive functional group-containing monomer include a monomer having a carbonyl group-containing group, an epoxy group-containing monomer, a hydroxy group-containing monomer, and an isocyanate group-containing monomer.
[0043] Examples of monomers having a carboxyl group-containing group include unsaturated dicarboxylic acids (maleic acid, itaconic acid, citraconic acid, crotonic acid, himic acid, 5-norbornene-2,3-dicarboxylic acid, maleic acid), their unsaturated dicarboxylic acid anhydrides, unsaturated monocarboxylic acids (acrylic acid, methacrylic acid), vinyl esters (vinyl acetate, vinyl chloroacetate, vinyl butanoate, vinyl pivalate, vinyl benzoate, vinyl crotonate), and the like.
[0044] Examples of the hydroxy group-containing monomer include hydroxy group-containing vinyl ester, hydroxy group-containing vinyl ether, hydroxy group-containing allyl ether, hydroxy group-containing (meth)acrylate, hydroxyethyl crotonate, and allyl alcohol.
[0045] Examples of the epoxy group-containing monomer include unsaturated glycidyl ethers (allyl glycidyl ether, 2-methylallyl glycidyl ether, vinyl glycidyl ether, etc.) and unsaturated glycidyl esters (glycidyl acrylate, glycidyl methacrylate, etc.).
[0046] Examples of the isocyanate group-containing monomer include 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethoxy)ethyl isocyanate, and 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate.
[0047] The amount of reactive functional groups contained in the fluorine-containing resin is preferably 0.01 to 3 mol %, more preferably 0.03 to 2 mol %, and even more preferably 0.05 to 1 mol % of all units constituting the fluorine-containing resin. If the amount of reactive functional groups is within the above range, the reactivity with the PAS resin is excellent and deterioration of flowability can be suppressed.
[0048] The structure of the fluorine-containing resin is not particularly limited, but is composed of at least one type of fluoroolefin unit. For example, tetrafluoroethylene polymer, copolymer with perfluoro(alkyl vinyl ether), hexafluoropropylene, vinylidene fluoride, vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene, and further copolymer with fluorine-free ethylene monomer such as ethylene, propylene, butene, alkyl vinyl ethers, etc. are listed. Specific examples include polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, etc. Among them, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer are preferred from the viewpoint of easy melt extrusion.
[0049] The melting point of the fluorine-containing resin used in the present invention is not particularly limited, but is preferably at least 230° C., more preferably at least 270° C. If the melting point of the fluorine-containing resin is within the above range, heat resistance can be maintained and good melt extrusion stability can be obtained.
[0050] The glass transition temperature of the fluorine-containing resin used in the present invention is not particularly limited, but is 130° C. or lower, more preferably 120° C. or lower, and more preferably 110° C. or lower. If the fluorine-containing resin has the above glass transition temperature, when a stretched film (one form of insulating substrate) is produced using a mixture with the PAS resin (A), peeling at the interface between the PAS resin (A) as a continuous phase and the fluorine-containing resin as a dispersed phase can be suppressed during stretching. This makes it possible to suppress breakage during stretching, and further to obtain a film having excellent mechanical properties.
[0051] [Modified elastomer (C)] The modified elastomer (C) is, in principle, contained in the dispersed phase of the resin composition constituting the insulating substrate (I). The modified elastomer (C) has a reactive group capable of reacting with at least one of the PAS resin (A) and the thermoplastic resin (B), and thus has the function of improving the mechanical strength (tensile properties, folding strength, etc.) of the laminate. In addition, it has excellent affinity with the styrene-based elastomer contained in the adhesive layer, thereby improving adhesion. The reactive group of the modified elastomer (C) is preferably at least one selected from the group consisting of an epoxy group and an acid anhydride group, and more preferably an epoxy group, which can rapidly react with the functional groups at the molecular ends of the PAS resin (A) and the thermoplastic resin (B).
[0052] Examples of such modified elastomers (C) include copolymers containing repeating units based on an α-olefin and repeating units based on a vinyl polymerizable compound having the above-mentioned functional group, and copolymers containing repeating units based on an α-olefin, repeating units based on a vinyl polymerizable compound having the above-mentioned functional group, and repeating units based on an acrylic ester.
[0053] Examples of the α-olefin include α-olefins having 2 to 8 carbon atoms, such as ethylene, propylene, and butene-1. Examples of the vinyl polymerizable compound having a functional group include α,β-unsaturated carboxylic acids and esters thereof, such as acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters; α,β-unsaturated dicarboxylic acids and esters thereof, such as maleic acid, fumaric acid, itaconic acid, and other unsaturated dicarboxylic acids having 4 to 10 carbon atoms, mono- or diesters thereof, and acid anhydrides thereof; α,β-unsaturated dicarboxylic acids, esters thereof, and acid anhydrides thereof; and α,β-unsaturated glycidyl esters.
[0054] The α,β-unsaturated glycidyl ester is not particularly limited, but examples thereof include a compound represented by the following formula (10).
[0055] [ka]
[0056] In the above formula, R 3 is an alkenyl group having 1 to 6 carbon atoms. Examples of the alkenyl group having 1 to 6 carbon atoms include a vinyl group, a 1-propenyl group, a 2-propenyl group, a 1-methylethenyl group, a 1-butenyl group, a 2-butenyl group, a 1-methyl-1-propenyl group, a 1-methyl-2-propenyl group, a 2-methyl-1-propenyl group, a 2-methyl-2-propenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, a 4-pentenyl group, a 1-methyl-1-pentenyl group, a 1-methyl-3-pentenyl group, a 1,1-dimethyl-1-butenyl group, a 1-hexenyl group, and a 3-hexenyl group.
[0057] R 4 are each independently a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2,2-dimethylpropyl group, a hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 4-methylpentyl group, a 2,2-dimethylbutyl group, a 2,3-dimethylbutyl group, a 2,4-dimethylbutyl group, a 3,3-dimethylbutyl group, and a 2-ethylbutyl group.
[0058] Specific examples of the α,β-unsaturated glycidyl ester include glycidyl acrylate and glycidyl methacrylate, with glycidyl methacrylate being preferred. The proportion of repeating units based on α-olefin in the modified elastomer (C) is preferably 50 to 95 mass%, more preferably 50 to 80 mass%. When the proportion of repeating units based on α-olefin is within the above range, the stretching uniformity, folding endurance, and adhesive strength with the adhesive layer of the film serving as the insulating substrate can be improved. The proportion of the repeating units based on the vinyl polymerizable compound having a functional group in the modified elastomer (C) is preferably 1 to 30 mass%, more preferably 2 to 20 mass%. When the proportion of the repeating units based on the vinyl polymerizable compound having a functional group is within the above range, not only the desired improvement effect but also good extrusion stability can be obtained.
[0059] The content of the modified elastomer (C) in the resin composition constituting the insulating substrate (I) is preferably 1 to 15 mass %, more preferably 2 to 10 mass %. When the content of the modified elastomer (C) is within the above range, the effect of improving the folding endurance, adhesive strength, etc. of the laminate is significantly exhibited.
[0060] [Silane coupling agent (D)] In the present invention, it is preferable to use a silane coupling agent as a component that has the function of increasing the compatibility and interaction between the PAS resin (A) and other components (the thermoplastic resin (B) other than the PAS resin, and the modified elastomer (C)). This dramatically improves the dispersibility of the other components in the PAS resin (A), enabling the formation of a good morphology.
[0061] The silane coupling agent (D) is preferably a compound having a functional group capable of reacting with a carboxyl group. Such a silane coupling agent reacts with other components to form a strong bond with them. As a result, the effect of the silane coupling agent is more pronounced, and the dispersibility of other components in the PAS resin (A) can be particularly improved. Examples of such silane coupling agents include compounds having an epoxy group, an isocyanate group, an amino group, or a hydroxyl group.
[0062] Specific examples of the silane coupling agent include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.
[0063] The content of the silane coupling agent in the resin composition constituting the insulating substrate (I) is preferably 0.01 to 5 mass %, more preferably 0.05 to 2.5 mass %. When the content of the silane coupling agent is within the above range, the effect of improving the dispersibility of other components in the PAS resin (A) is significantly exhibited.
[0064] [Metal layer (I), (II)] As the metal layer (conductor layer), foils of copper, aluminum, iron, gold, silver, nickel, palladium, chromium, molybdenum, or alloys thereof are preferably used. Among them, copper foil is preferred from the viewpoints of workability, flexibility, electrical conductivity, etc. Examples of copper foil include rolled copper foil and electrolytic copper foil. The thickness of the copper foil is preferably 1 μm or more and 50 μm or less, more preferably 1 μm or more and 30 μm or less. The copper foil may also be subjected to various surface treatments (roughening, rust-proofing, etc.). Examples of rust-proofing treatments include mirror-finishing treatments such as plating treatments containing Ni, Zn, Sn, etc., and chromate treatments. The metal layer (I) and the metal layer (II) may be either the same metal layer or different metal layers.
[0065] In order for a circuit board using the copper-clad laminate obtained by the present invention to exhibit good high-frequency characteristics, it is preferable that the surface roughness of the metal layer (I) on the side in contact with the insulating substrate (I) is low. The surface roughness Rz of the metal layer (I) on the side in contact with the insulating substrate (I) is preferably 2 μm or less, more preferably 1.5 μm or less, and even more preferably not roughened.
[0066] [Adhesive layer] The adhesive layer is used for interlayer adhesion of multilayer flexible wiring boards and for adhesion of reinforcing plates of flexible wiring boards, and is called a bonding sheet. It is not particularly limited, but from the viewpoints of good adhesion to the circuit formation layer formed from the metal layer (I) and the insulating substrate (I) made of a resin composition mainly composed of a polyarylene sulfide resin, excellent conformability for embedding the circuit pattern, and low dielectric properties, it is preferable to use a thermosetting resin containing a styrene-based elastomer as the main component. In addition to the thermosetting resin, additives such as a curing agent, a curing accelerator, a flexible component, an inorganic filler, and a flame retardant may be included as necessary.
[0067] The styrene elastomer is a copolymer of styrene and an olefin (e.g., a conjugated diene such as butadiene or isoprene) and / or a hydrogenated product thereof. The styrene elastomer is a block copolymer with styrene as a hard segment and a conjugated diene as a soft segment. Examples of the styrene elastomer include styrene / butadiene / styrene block copolymer, styrene / isoprene / styrene block copolymer, styrene / ethylene / butylene / styrene block copolymer, styrene / ethylene / propylene / styrene block copolymer, and styrene / butadiene block copolymer. In addition, styrene / ethylene / butylene / styrene block copolymer, styrene / ethylene / propylene / styrene block copolymer, and styrene / butadiene block copolymer (also called hydrogenated styrene elastomer), which are obtained by removing the double bond of the conjugated diene component by hydrogenation, may be used. One or more types of styrene elastomers may be used in combination.
[0068] The styrene-based elastomer may have a functional group such as a carboxyl group or a glycidyl group. The modification of the styrene-based elastomer containing a functional group can be carried out, for example, by copolymerizing an unsaturated carboxylic acid during polymerization of the styrene-based elastomer. It can also be carried out by heating and kneading the styrene-based elastomer and the unsaturated carboxylic acid in the presence of an organic peroxide. Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, itaconic acid, fumaric acid, maleic anhydride, itaconic anhydride, and fumaric anhydride. The amount of modification by the unsaturated carboxylic acid is preferably 0.1 to 10% by mass.
[0069] The weight average molecular weight of the styrene-based elastomer is preferably 10,000 or more, more preferably 100,000 to 300,000, and even more preferably 50,000 to 250,000. By adopting such a configuration, it is possible to improve the adhesive strength (connection reliability), flexibility, and conformability.
[0070] The styrene ratio in the styrene-based elastomer is preferably less than 50%, more preferably 5 to 45%, and even more preferably 10 to 40%. By adopting such a constitution, it is possible to improve the bending resistance, adhesive strength (connection reliability), bending property, and conformability.
[0071] The content of the styrene-based elastomer in the adhesive layer is preferably 50% by mass or more based on 100% by mass of the solid content of the adhesive layer. If it is less than 50% by mass, the adhesive strength, flex resistance, and followability are deteriorated.
[0072] As the thermosetting resin containing a styrene-based elastomer, one or more of known thermosetting resins can be used in combination. In particular, epoxy-based compounds are preferably used from the viewpoint of heat resistance. The epoxy-based compound may contain at least two or more epoxy groups in the molecule, and examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AD type epoxy resin, resorcin type epoxy resin, hydroquinone type epoxy resin, catechol type epoxy resin, hydroxynaphthalene type epoxy resin, biphenyl type epoxy resin, tetramethylbiphenyl type epoxy resin, phenol novolac type epoxy resin, and cresol novolac type epoxy resin. The epoxy resin may be used alone or in combination of two or more.
[0073] Examples of the curing agent include amine compounds such as dicyandiamide, diaminodiphenylmethane, diaminodiphenyl sulfide, diaminobenzophenone, diaminodiphenyl sulfone, and diethyltriamine, imidazole derivatives such as 2-alkyl-4-methylimidazole, 2-phenyl-4-alkylimidazole, 2-phenyl-4-alkylimidazole, and 1-cyanoethyl-2-methylimidazole, DBU compounds such as 1,8-diazabicyclo[5,4,0]undecene and 7,1,4-diazabicyclo[2,2,2]octane, phosphorus compounds such as triphenylphosphine and triethylphosphine, benzyldimethylamine, 2-(dimethylamino)phenol, and the like. Examples of the fluorinated organic compounds include aromatic tertiary amines such as 4,6-tris(diaminomethyl)phenol, alicyclic tertiary amines such as dimethylcyclohexylamine, organic acids such as phthalic anhydride, trimellitic anhydride, and pyromellitic acid, amine complexes of boron trifluoride such as boron triethylamine complex and boron trifluoride piperazine complex, amine complexes of boron trichloride, amine complexes of boron trifluoride such as phosphorus pentafluoride, arsenic pentafluoride, antimony pentafluoride, boron tetrafluoride amine complex, and boron trifluoride piperazine complex, amine complexes of boron trichloride, phosphorus pentafluoride, arsenic pentafluoride, antimony pentafluoride, boron tetrafluoride amine salt, and metal fluorinated borate such as zinc fluorinated borate. These may be used alone or in combination of two or more. Furthermore, phenolic resins such as resol type and novolac type phenolic resins may be used. Examples of the phenolic resin include alkyl-substituted phenols such as phenol, biphenol, and cresol; cyclic alkyl-modified phenols such as terpene and dicyclopentadiene; those having a functional group containing a hetero atom such as a nitro group or an amino group; and those having a skeleton such as naphthalene or anthracene.
[0074] In addition to the above-mentioned thermosetting resin, a curing accelerator, an elastic component, an inorganic filler, and a flame retardant may be added as necessary.
[0075] Known materials can be used as the elastic component. For example, various synthetic rubbers such as acrylic rubber, acrylonitrile butadiene rubber, and carboxyl-containing acrylonitrile butadiene rubber, rubber-modified high molecular weight compounds, modified polyimides, modified polyamide-imides, polyurethane resins, polyester resins, polyurethane polyester resins, polyvinyl butyral resins, polyvinyl acetoacetal resins, and phenoxy resins can be used. These components can be used alone or in combination of two or more.
[0076] As the inorganic filler, known fillers can be used, such as silica, alumina, silicon nitride aluminum hydroxide, magnesium hydroxide, talc, clay, etc. These fillers can be used alone or in combination of two or more kinds.
[0077] Known flame retardants can be used. For example, phosphorus atom-containing compounds, nitrogen atom-containing compounds, inorganic flame retardant compounds, etc. can be mentioned. Specific examples include phosphorus atom-containing compounds such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, tri-2-ethylhexyl phosphate, tributoxyethyl phosphate, triphenyl phosphate, tricresyl phosphate, and trixylenyl phosphate, ammonium polyphosphate, polyphosphoric acid amide, red phosphorus, guanidine phosphate, and condensed phosphoric acid ester compounds such as dialkyl hydroxymethyl phosphonate, nitrogen atom-containing compounds such as melamine, and inorganic flame retardant compounds such as aluminum hydroxide, magnesium hydroxide, zinc borate, and calcium borate. These components can be used alone or in combination of two or more.
[0078] The thickness of the adhesive layer after curing is preferably from 1 μm to 100 μm, more preferably from 5 μm to 70 μm, and even more preferably from 10 μm to 50 μm.
[0079] After the adhesive layer is cured, the dielectric constant is preferably 3.5 or less and the dielectric loss tangent is 0.01 or less at a frequency of 5 GHz.More preferably, the dielectric constant is 3.5 or less and the dielectric loss tangent is 0.007 or less.If the dielectric constant is 3.5 or less and the dielectric loss tangent is 0.01 or less, the adhesive can be suitably used in FPC-related products that have strict requirements for electrical properties.
[0080] [Insulating substrate (II)] The resin composition constituting the insulating substrate (II) may be any substrate made of various polymers such as polyimide, liquid crystal polymer, polycarbonate, polyphenylene ether, polyethersulfone, polyphenylsulfone, polyetherimide, polysulfone, and fluorine-containing resin, or a blend containing at least one of these polymers, and may be the insulating substrate (I).
[0081] [Additives for insulating base material (I)] The resin composition of the insulating substrate (I) may contain a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, an ultraviolet stabilizer, a lubricant, an antistatic agent, a colorant, a conductive agent, a flame retardant, etc., as long as the effects of the present invention are not impaired.
[0082] The method for producing the resin composition of the insulating substrate (I) is not particularly limited, but examples thereof include a method in which the PAS resin (A) and other components (thermoplastic resin (B) other than the PAS resin), and other components as necessary (modified elastomer (C), silane coupling agent (D), etc.) are uniformly mixed in a tumbler or Henschel mixer, and then the mixture is charged into a twin-screw extruder for melt-kneading. This melt-kneading may be either kneading in a shear flow field or kneading in an extensional flow field, or both. This melt kneading is preferably carried out under conditions where the ratio of the discharge rate (kg / hr) of the kneaded material to the screw rotation speed (rpm) (discharge rate / screw rotation speed) is 0.02 to 0.2 (kg / hr·rpm).
[0083] More specifically, it is preferable to feed each component into a twin-screw extruder and melt-knead it under temperature conditions of a set temperature of 300°C and a resin temperature of about 330°C in the strand die. In this case, the discharge rate of the kneaded product is in the range of 5 to 50 kg / hr at a rotation speed of 250 rpm. In particular, from the viewpoint of increasing the dispersibility of each component, it is preferable that the discharge rate of the kneaded product is 20 to 35 kg / hr at a rotation speed of 250 rpm. Therefore, it is more preferable that the ratio of the discharge rate of the kneaded product (kg / hr) to the screw rotation speed (rpm) (discharge rate / screw rotation speed) is 0.08 to 0.14 (kg / hr rpm).
[0084] [Insulating substrate (I) (film) mainly composed of PAS resin (A)] One of the forms of the insulating substrate (I) of the present invention is a film obtained from a resin composition mainly composed of a PAS resin (A), and among them, a biaxially stretched film is preferable. By using a biaxially stretched film, heat resistance can be improved. In one embodiment of such a film, the PAS resin (A) serves as a matrix (continuous phase), and particles (dispersed phase) containing a thermoplastic resin (B) other than the PAS resin are dispersed in this matrix. The modified elastomer (C) is present on the surface of the particles of the thermoplastic resin (B) (i.e., the interface between the matrix and the particles), inside the particles of the thermoplastic resin (B), or as particles (dispersed phase) separate from the particles of the thermoplastic resin (B).
[0085] The present inventors also believe that the modified elastomer (C) also functions as a compatibilizer between the PAS resin (A) and the thermoplastic resin (B), and thus the particles are finely dispersed in the matrix, suppressing the film from breaking during stretching, improving the mechanical strength (folding endurance, etc.) of the biaxially stretched film, and improving the mechanical strength of the laminate. In addition, the modified elastomer (C) has excellent affinity with the styrene-based elastomer contained in the adhesive layer, improving adhesion. Furthermore, it is believed that the combined use of the modified elastomer (C) with the silane coupling agent further improves the adhesiveness at the interface between the matrix and the particles, and further improves the mechanical strength (folding endurance, etc.) of the biaxially stretched film and the laminate.
[0086] The average particle size (average dispersion diameter) of the particles (dispersed phase) dispersed in the matrix in the film state is preferably 5 μm or less, more preferably 0.5 μm or more and 5 μm or less, and even more preferably 0.5 μm or more and 3 μm or less. If the average particle size of the particles is within the above range, the performance as a biaxially stretched film and a substrate is maintained, and the adhesion to the metal layer (I) (II) and the adhesive layer is good.
[0087] The film is preferably a biaxially stretched film obtained by biaxially stretching an unstretched sheet obtained from the resin composition constituting the insulating substrate (I).
[0088] The biaxially stretched film may have at least one layer made of the resin composition constituting the insulating substrate (I) of the present invention as the outermost layer, and may be a multilayer film in which a layer made of another resin composition is laminated directly or via an adhesive layer or the like.
[0089] The method for producing the biaxially stretched laminate film used in the present invention is not particularly limited, but for example, in the case of a laminated structure, the resins or resin mixtures used for each resin layer are heated and melted in separate extruders, laminated in the molten state in the desired laminated structure by a coextrusion lamination die method, a feed block method, or the like, and then molded into a sheet by an inflation method, a T-die chill roll method, etc. This coextrusion method is preferable because it allows relatively free adjustment of the thickness ratio of each layer and can produce an unstretched laminated sheet with excellent cost performance.
[0090] Next, in the case of biaxial stretching, the unstretched sheet and the unstretched laminate sheet obtained above are biaxially stretched. The stretching method may be a sequential biaxial stretching method, a simultaneous biaxial stretching method, or a combination of these methods. When biaxially stretching is performed by the sequential biaxial stretching method, for example, the obtained unstretched sheet is heated with a group of heating rolls and stretched in the longitudinal direction (MD direction) by 1.5 to 4 times (preferably 2 to 3.8 times) in one stage or in two or more stages, and then cooled with a group of cooling rolls at 30 to 60°C. The stretching temperature is preferably from the glass transition temperature (Tg) of the PAS resin (A) to Tg+40°C, more preferably from Tg+5°C to Tg+30°C, and even more preferably from Tg+5°C to Tg+20°C.
[0091] Next, the film is stretched in the transverse direction (TD) by using a tenter. Both ends of the film stretched in the MD are held by clips and introduced into the tenter, where it is stretched in the TD. The stretching ratio is preferably 1.5 to 4 times, and more preferably 2 to 3.8 times. The stretching temperature is preferably from Tg to Tg+40°C, more preferably from Tg+5°C to Tg+30°C, and further preferably from Tg+5°C to Tg+20°C.
[0092] The stretched film is then heat set while under tension or relaxed in the width direction. The heat setting temperature is not particularly limited, but is preferably 200 to 280°C, more preferably 220 to 280°C, and even more preferably 240 to 275°C. The heat setting may be carried out in two stages by changing the heat setting temperature. In this case, it is preferable that the heat setting temperature in the second stage is higher by +10 to 40°C than the heat setting temperature in the first stage. A stretched film heat set at a heat setting temperature in this range has improved heat resistance and mechanical strength. The heat setting time is preferably 1 to 60 seconds.
[0093] Furthermore, this film is cooled while being relaxed in the width direction in a temperature zone of 50 to 275° C. The relaxation rate is preferably 0.5 to 10%, more preferably 2 to 9%, and further preferably 3 to 8%.
[0094] In order to improve the thermal stability of the film, a heat treatment (annealing treatment) may be further performed. Examples of heat treatment methods after stretching include known methods such as a method of blowing hot air, a method of irradiating infrared rays, and a method of irradiating microwaves. Among them, a method of blowing hot air is preferable because it can heat uniformly and accurately. The heat treatment temperature is preferably 150 to 260°C, and more preferably 160 to 240°C. If the above heat treatment is not performed, it is difficult to relax the stress of the film, and a heat treatment at a temperature of 150°C or less cannot sufficiently relax the stress, and the thermal shrinkage rate of the film after production cannot be reduced. As a result, it is difficult to improve the thermal stability of the film. In addition, if the heat treatment temperature is 260°C or more, melting of a part of the crystalline phase of polyphenylene sulfide progresses, and the orientation is broken. Therefore, the linear expansion coefficient in the plane direction of the film after production is deteriorated. As a result, it is difficult to improve the thermal stability of the film. The heat treatment time is preferably 3 to 300 seconds, and more preferably 5 to 100 seconds.
[0095] The thickness of the biaxially stretched film or biaxially stretched laminate film (hereinafter, both biaxially stretched films may be referred to as "stretched film") is not particularly limited, but is preferably 10 to 300 μm, more preferably 10 to 200 μm, and even more preferably 10 to 150 μm. A stretched film of such a thickness can provide a substrate with sufficient mechanical strength and insulating properties.
[0096] In order to enhance the adhesion between the stretched film of the present invention and the copper foil or adhesive layer, the stretched film may be subjected to a surface treatment, such as corona discharge treatment (including corona treatment under various gas atmospheres), plasma treatment (including plasma treatment under various gas atmospheres), and oxidation treatment using chemicals, ultraviolet rays, electron irradiation, etc.
[0097] [Circuit formation] The circuit-forming layer of the present invention is formed from a laminate consisting of an insulating substrate (I) and a metal layer (I). The circuit-forming method is not particularly limited, and examples thereof include a method of forming an unpatterned metal layer (I) and then patterning it by etching or the like, a method of directly forming a metal layer (I) at a location required for the circuit pattern on the insulating substrate, and a method combining both, and the like, and the circuit-forming layer can be formed by a subtractive method, a semi-additive method, a full-additive method, or the like.
[0098] In the laminate of the present invention consisting of the insulating substrate (I) and the metal layer (I), the metal layer (I) is laminated directly on the insulating substrate (I) or via an adhesive layer or a bonding layer. For example, there is a method of laminating the insulating substrate (I) and the copper foil by thermal lamination, a method of applying a resin solution for forming an adhesive layer to the surface of the insulating substrate (I) and drying it, or a method of thermally laminating a film made of an adhesive to the insulating substrate (I) to form an uncured adhesive layer, and then bonding the adhesive layer side to the copper foil.
[0099] Alternatively, a nickel alloy may be used as the adhesion layer. Among them, a nickel-copper alloy is preferable from the viewpoint of etching property and adhesion, and is suitable for a high-frequency circuit board. As a method for forming an adhesion layer made of a nickel alloy, for example, a method of treating the entire surface of the insulating base material (I) using various sputtering methods, represented by DC magnetron sputtering, vapor deposition, ion plating, etc., using a nickel-copper alloy as a material, etc., may be mentioned. After forming the adhesion layer, it is made into a metal layer (I) such as copper of a predetermined thickness by electrolytic plating.
[0100] The thickness of the adhesive layer is preferably 3 nm or more and 100 nm or less. Since nickel alloys have poorer electrical conductivity than copper, if the thickness of the adhesive layer is thicker than 100 nm, it may adversely affect signal transmission.
[0101] In one embodiment, the laminate may have a configuration of metal layer (I)-insulating substrate, metal layer (I)-adhesive layer-insulating substrate, metal layer (I)-adhesive layer-insulating substrate, metal layer (I)-insulating substrate-metal layer (I), metal layer (I)-adhesive layer-insulating substrate-adhesive layer-metal layer (I), metal layer (I)-adhesive layer-insulating substrate-adhesive layer-metal layer (I), metal layer (I)-adhesive layer-insulating substrate-adhesive layer-metal layer (I), metal layer (I)-adhesive layer-stretched substrate-adhesive layer-metal layer (I)-adhesive layer-insulating substrate, ... or the like.
[0102] [Circuit evaluation] 1. Dielectric properties of insulating substrate (I) The dielectric constant and dielectric loss tangent were measured based on the cavity resonance method specified in JIS C 2565:1992. Specifically, a strip of 3 mm width x 150 mm length was prepared from the insulating substrate (I). The prepared strip was then left to stand for 24 hours under an environment of 23°C and 50% Rh, and the dielectric constant and dielectric loss tangent at a frequency of 5 GHz were measured by the cavity resonance method using ADMS010c series (manufactured by AET Corporation). The dielectric characteristics of the insulating substrate of the high-frequency circuit board are preferably a dielectric constant of 3.3 or less and a dielectric loss tangent of 0.005 or less at a frequency of 5 GHz.
[0103] 2. Adhesion to adhesive layer The adhesive layer (thickness 25μm, 100×100mm) and the insulating substrate (I) (100×100mm) are overlapped, and pressed at 80℃ under 0.5MPa for 1 minute in a press machine, then cured at 180℃ / 30 minutes to create a laminate of the bonding sheet and insulating substrate. A sample of width 10mm×length 70mm is cut out from the laminate, and a peel test is performed using a tensile tester with a chuck distance of 50mm and a tensile speed of 50mm / min to determine and evaluate the maximum adhesive strength. If the adhesive strength is 5N / cm or more, peeling during processing such as circuit formation by etching, through-hole formation, and desmearing, as well as swelling and peeling during reflow, can be suppressed. ◎;6N / cm or more ○: 5N / cm or more and less than 6N / cm ×: Less than 5N / cm
[0104] 3.Reflow resistance The wiring board is subjected to a reflow process three times with a top temperature of 260°C for 30 seconds, and the appearance of the sample after the process is observed to evaluate swelling and peeling. 〇: No swelling or peeling ×: Swelling and peeling
[0105] 4. Transmission Loss Transmission loss was measured using a wiring board with a strip structure. Transmission loss was measured up to 40GHz using a network analyzer (KEYSIGHT TECNOLOGIES) with a probe method. By using a low dielectric insulating base material, a low dielectric bonding sheet, and a low roughness metal layer (I), transmission loss can be reduced, and a loss of less than -10.0dB at a frequency of 40GHz makes it an excellent high-frequency circuit board. EXAMPLES
[0106] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these. 1. Production of resin composition and biaxially stretched film (insulating substrate (I)) [Example 1] A mixture was obtained by uniformly mixing 84.5 mass% polyphenylene sulfide resin (A) (manufactured by DIC Corporation, linear type, melting point 285°C, melt viscosity (V6) at 300°C 160 Pa s), 15 mass% polyphenylene ether resin (B) (manufactured by Mitsubishi Engineering Plastics Corporation, glass transition temperature 210°C, hereinafter sometimes referred to as "PPE"), and 0.5 mass% 3-glycidoxypropyltriethoxysilane in a tumbler.
[0107] The polyphenylene sulfide resin has a carboxyl group at its molecular terminal. Hereinafter, polyphenylene sulfide resin will be referred to as "PPS" and 3-glycidoxypropyltriethoxysilane will be referred to as "Silane coupling agent-1."
[0108] Next, the mixture obtained above was put into a vented twin screw extruder (manufactured by The Japan Steel Works, Ltd., "TEX-30α"), and then melt extruded under conditions of a discharge rate of 20 kg / hr, a screw rotation speed of 300 rpm, a cylinder set temperature of 300°C, and a resin temperature at the strand die of about 300°C, and discharged in the form of a strand, which was then cooled with water at a temperature of 30°C and cut to produce a resin composition.
[0109] Next, this resin composition was dried at 140° C. for 3 hours, and then charged into a full-flight screw single-screw extruder and melted under conditions of 280 to 310° C. The molten resin composition was extruded from a T-die and then cooled in close contact with a chill roll set at 40° C. to produce an unstretched sheet. Next, the produced unstretched sheet was biaxially stretched 3.0x3.0 times at 100°C using a batch-type biaxial stretching machine (manufactured by Imoto Manufacturing Co., Ltd.) to obtain a film with a thickness of 50 μm. Furthermore, the obtained film was fixed to a mold and heat-set in an oven at 275°C to produce an insulating substrate (I) of a biaxially stretched film.
[0110] The biaxially stretched film was then passed through an infrared heating furnace (corresponding to an annealing furnace) with a heating distance of 2.0 m, cooled to room temperature, and wound into a roll to obtain an annealed biaxially stretched film (insulating substrate (I)). The treatment conditions were an oven temperature of 200°C, treatment time of 60 seconds, and tension of 10 N.
[0111] The obtained insulating substrate (I) was subjected to sputtering under argon gas using a nickel-copper alloy containing 35% by mass of copper to form an adhesion layer with an average thickness of 10 nm, and further subjected to plating to form a metal layer (I) (conductor layer) with a thickness of 12 μm, thereby producing a double-sided copper-clad laminate and a single-sided copper-clad laminate.
[0112] The average particle size of the particles in the produced resin composition was measured as follows. The resin composition pellets were cut perpendicular to the flow direction by ultra-thin sectioning. Next, scanning electron microscope (SEM) photographs of the cut surfaces of the cut pellets were taken at 2000 times magnification, and the obtained images were enlarged to A3 size. Next, 50 particles were selected from the enlarged SEM photographs, and the maximum diameter of each particle on the cut surface was measured to calculate the average particle size. As a result, the average particle size of the particles of the resin composition pellets was 1.3 μm.
[0113] In addition, the resin pellets made of the resin composition obtained above were subjected to SEM-EDS analysis to analyze the components constituting the matrix and particles of the resin composition pellets. As a result, it was found that the component constituting the matrix was PPS, and the component constituting the dispersed particles was PPE resin.
[0114] Next, a circuit was formed on the obtained double-sided copper-clad laminate using a subtractive method, and a bonding sheet ("NIKAFLEX SAFY", manufactured by Nikkan Industrial Co., Ltd., thickness 25 μm, relative dielectric constant 3.0, dielectric tangent 0.005) was attached to the circuit side, and then a single-sided copper-clad plate was laminated to create a wiring board with a strip structure designed to have a characteristic impedance of 50.
[0115] [Example 2] The adhesive side of a copper foil with a low dielectric adhesive (ZAC-LDC manufactured by Fujimori Kogyo) having an adhesive thickness of 5 μm was press-bonded to an insulating substrate (I) at 150°C, 3 MPa, and 1 minute, and then cured at 200°C for 60 minutes to obtain a double-sided copper-clad laminate and a single-sided copper-clad laminate. Except for this, a wiring board was obtained in the same manner as in Example 1.
[0116] [Example 3] A wiring board was obtained in the same manner as in Example 1, except that the insulating substrate (I) and copper foil (Fukuda Metal, electrolytic copper foil 12 μm, Rz 1.2 μm) were directly overlapped, and the biaxially oriented film and copper foil were thermocompression-bonded under conditions of 270° C. / 5 MPa using a heat press to obtain a double-sided copper-clad laminate and a single-surface laminate.
[0117] [Example 4] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was 94.5% by mass, and the thermoplastic resin (B) was 5% by mass of polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Chemical Co., Ltd., glass transition temperature 145°C, sometimes referred to as "PC" hereinafter).
[0118] [Example 5] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was 89.5% by mass, and the thermoplastic resin (B) was 10% by mass of polyethersulfone resin (manufactured by BASF Ltd., glass transition temperature 225°C, sometimes referred to as "PES" hereinafter).
[0119] [Example 6] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that a polyphenylsulfone resin (manufactured by BASF Ltd., glass transition temperature 220°C, hereinafter sometimes referred to as "PPSU") was used as the thermoplastic resin (B).
[0120] [Example 7] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was 94.5% by mass, and the thermoplastic resin (B) contained 5% by mass of polyetherimide resin (manufactured by SABIC Corporation, glass transition temperature 216°C, sometimes referred to as "PEI").
[0121] [Example 8] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that a polysulfone resin (manufactured by SOLVAY Corporation, glass transition temperature 190°C, hereinafter sometimes referred to as "PSU") was used as the thermoplastic resin (B).
[0122] [Example 9] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that a modified fluororesin having a functional group (hereinafter sometimes referred to as "modified PFA"; manufactured by AGC Inc., Tg 94°C) was used as the thermoplastic resin (B) and 3-isocyanatepropyltriethoxysilane was used as the silane coupling agent. Hereinafter, 3-isocyanatepropyltriethoxysilane will be referred to as "Silane coupling agent-2."
[0123] [Example 10] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was 74.5% by mass, the thermoplastic resin (B) contained 10% by mass of PPE resin, 15% by mass of modified PFA resin, and 0.5% by mass of silane coupling agent-2.
[0124] [Example 11] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was 82.5% by mass, the thermoplastic resin (B) was 15% by mass of PPE resin, and the modified elastomer (C) was 2% by mass of Bondfast 7L (manufactured by Sumitomo Chemical Co., Ltd., ethylene / glycidyl methacrylate / methyl acrylate = 70 / 3 / 27 (mass %), hereinafter sometimes referred to as "BF7L").
[0125] [Example 12] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that 3-aminopropyltriethoxysilane was used as the silane coupling agent. Hereinafter, 3-aminopropyltriethoxysilane will be referred to as "Silane coupling agent-3."
[0126] [Example 13] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was 85% by mass, the thermoplastic resin (B) was 15% by mass of PPE resin, and no silane coupling agent was added.
[0127] [Comparative Example 1] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that a biaxially stretched film made only of PPS resin was used as the insulating substrate (I).
[0128] [Comparative Example 2] A double-sided copper-clad laminate, a single-surface laminate, and a wiring board were obtained in the same manner as in Example 1, except that a polyimide adhesive ("PIAD" manufactured by Arakawa Chemical Industry Co., Ltd.) was used as the adhesive layer.
[0129] [Comparative Example 3] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that polyimide (Kapton manufactured by DuPont, thickness 50 μm) was used as the insulating base material (I).
[0130] [evaluation] Dielectric properties of insulating substrate (I) The dielectric constant and dielectric loss tangent were measured based on the cavity resonance method specified in JIS C 2565:1992. Specifically, a strip of 3 mm width × 150 mm length was prepared from the insulating substrate (I). The prepared strip was then left to stand for 24 hours in an environment of 23°C and 50% RH, and the dielectric constant and dielectric loss tangent at a frequency of 5 GHz were measured by the cavity resonance method using ADMS010c series (manufactured by AET Corporation).
[0131] 2. Adhesion to adhesive layer The adhesive layer (bonding sheet) (thickness 25μm, 100×100mm) and the insulating substrate (I) (100×100mm) are overlapped, pressed at 80℃ under 0.5MPa for 1 minute in a press, and then cured at 180℃ / 30 minutes to produce a laminate of the bonding sheet and film. A sample with a width of 10mm and a length of 70mm is cut out from the wiring board, and a peel test is performed on a tensile tester with a chuck distance of 50mm and a tensile speed of 50mm / min to determine and evaluate the maximum adhesive strength. ◎;6N / cm or more ○: 5N / cm or more and less than 6N / cm ×: Less than 5N / cm
[0132] 3.Reflow resistance The wiring board is put through a reflow process three times with a top temperature of 260°C for 30 seconds, and the appearance of the sample after the process is observed to evaluate swelling and peeling. 〇: No swelling or peeling ×: Swelling and peeling
[0133] 4. Transmission Loss The transmission loss was measured using a wiring board with a strip structure. The transmission loss was measured up to 40 GHz using a network analyzer (Keysight Technologies) with a probe method.
[0134] [Table 1] *PPS: Polyphenylene sulfide resin PPE; Polyphenylene ether resin PC; polycarbonate resin PES; Polyethersulfone resin PPSU; Polyphenylsulfone resin PEI; Polyetherimide resin PSU; Polysulfone resin Modified PFA; Modified perfluoroalkoxyalkane
[0135] [Table 2]
[0136] [Table 3]
[0137] [Table 4] *PI; Polyimide
[0138] The circuit boards obtained in Examples 1 to 13 exhibited excellent adhesion and heat resistance. In contrast, the circuit boards obtained in Comparative Examples 1 and 2 were inferior in adhesion and reflow resistance (heat resistance). In addition, the circuit boards obtained in Examples 1 to 13 had lower transmission losses than Comparative Example 3.
Claims
1. A circuit board including at least a metal layer (I), an insulating substrate (I) having a circuit formed on one or both sides, an adhesive layer on the circuit forming surface side, and an insulating substrate (II) or a metal layer (II) laminated in this order, The insulating substrate (I) is made of a resin composition including a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher, The circuit board, wherein the adhesive layer is a thermosetting resin layer containing a styrene-based elastomer.
2. 2. The circuit board according to claim 1, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is a dispersed phase having an average dispersed diameter of 5 [mu]m or less.
3. The circuit board according to claim 1 or 2, wherein the blending ratio of the thermoplastic resin (B) other than the polyarylene sulfide-based resin is in the range of 1 to 49 mass% relative to 100 mass% of the total amount of the polyarylene sulfide-based resin (A) and the thermoplastic resin (B).
4. 3. The circuit board according to claim 1, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is a polyphenylene ether resin, a polycarbonate resin, a polyethersulfone resin, a polyphenylenesulfone resin, a polyetherimide resin, a polysulfone resin or a fluorine-containing resin.
5. 3. The circuit board according to claim 1, wherein the insulating substrate (I) has a dielectric constant of 3.3 or less.
6. 3. The circuit board according to claim 1, further comprising a modified elastomer (C) having reactive groups added to the resin composition of the insulating substrate (I).
7. 7. The circuit board according to claim 6, wherein the modified elastomer (C) comprises an olefin polymer having at least one functional group selected from the group consisting of an epoxy group and an acid anhydride group.
8. The circuit board according to claim 6, wherein the blending ratio of the modified elastomer (C) is 1 to 15 mass% relative to 100 mass% in total of the polyarylene sulfide-based resin (A), the thermoplastic resin other than polyarylene sulfide (B), and the modified elastomer (C).
9. 7. The circuit board according to claim 6, wherein the modified elastomer (C) has an α-olefin content of 50 to 95% by mass based on the total mass of the modified elastomer.
10. 3. The circuit board according to claim 1, further comprising 0.01 to 5 mass % of a silane coupling agent (D) containing at least one functional group selected from the group consisting of an epoxy group, an amino group, and an isocyanate group.
11. 3. A high-speed transmission cable comprising the circuit board according to claim 1 or 2.
Citation Information
Patent Citations
Circuit board and manufacturing method thereof
JP2022039457A
Cited By
Arrangement members and detection modules
JP2026157345A